Observation of B -> K-S(0)pi(+)pi(-) and evidence for B -> K-*+/-pi(-/+) - Eckhart, E; Gan, K; Gwon, C; Hart, T; Honscheid, K; Hufnagel, D; Kagan, H; Kass, R; Pedlar, T; Thayer, J; von Toerne, E; Wilksen, T; et al. (2002)
The three-body decay Β→K0π+π- with a branching fraction (50-9+10±7)X10-6 was observed. A simultaneous analysis of the Dalitz plots for this decay and for Β→K+π-π0 revealed the presence of Β→K*+(892)π- with a branching fraction (16-5+6±2)X10-6, which is larger than but consistent with most theoretical predictions.